2022
DOI: 10.1093/molbev/msac158
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Signals of Positive Selection in Peruvian Populations from Three Ecological Regions

Abstract: Perú hosts extremely diverse ecosystems which can be broadly classified into three major ecoregions: the Pacific desert coast, the Andean highlands, and the Amazon rainforest. Since its initial peopling approximately 12,000 years ago, the populations inhabiting such ecoregions might have differentially adapted to their contrasting environmental pressures. Previous studies have described several candidate genes underlying adaptation to hypobaric hypoxia among Andean highlanders. However, the adaptive genetic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 138 publications
1
10
1
Order By: Relevance
“…BRINP3 is thought to be important for adaptation to hypoxic conditions via the cardiovascular system and has been identified for high probability of recent positive selection in Bolivian Aymara and highland Peruvian populations. 8 , 33 All other genes with SNPs under high probability of selection related to hypoxia or cardiovascular function in our study differed from those identified in other Andean and worldwide high-altitude population studies ( Table S6 ). 8 , 9 , 10 This suggests there are more complex modes of genetic adaptation to hypoxic conditions in the Andes that are yet to be understood.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…BRINP3 is thought to be important for adaptation to hypoxic conditions via the cardiovascular system and has been identified for high probability of recent positive selection in Bolivian Aymara and highland Peruvian populations. 8 , 33 All other genes with SNPs under high probability of selection related to hypoxia or cardiovascular function in our study differed from those identified in other Andean and worldwide high-altitude population studies ( Table S6 ). 8 , 9 , 10 This suggests there are more complex modes of genetic adaptation to hypoxic conditions in the Andes that are yet to be understood.…”
Section: Discussioncontrasting
confidence: 73%
“… 10 , 11 However, this particular EGLN3 SNP from the present study has yet to be characterized in the functional genomics literature, though EGLN3 was recently also identified as being under selection in highland populations in Peru, as was the GALNT13 gene. 33 In addition, an SNP near the BRINP3 gene was identified as a candidate for positive selection in the present study in the Loja analysis group. BRINP3 is thought to be important for adaptation to hypoxic conditions via the cardiovascular system and has been identified for high probability of recent positive selection in Bolivian Aymara and highland Peruvian populations.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations